Johna Locke’a koncepcja wychowania moralnego - Raniszewska-Wyrwa, Agnieszka (Biuletyn Historii Wychowania, 2014)
John Locke was an English philosopher, doctor and politician who also contributed to the developmen of educational thinking. His school experiences, as well as those acquired in the role of a teacher, were the impulse behind his deliberations on education. The letters to Edward Clarke, forming an answer to Clarke’s request that he guide his children’s upbringing, provided the opportunity for him to present them. The content that Locke included in his letters was, in time, repeated in Some Thoughts Concerning Education. The ideas on descent and the limits of human cognition presented in his philosophical works are closely related with his views on education. In An Essay Concerning Human Understanding Locke stated that the human mind at the moment of birth is a blank slate (tabula rasa), which through life is filled by experiences. As a result, he attributed much importance to education – it is an integral part of the process of filling the mind with content, and through this shaping the person. Locke stressed that most people are “good or bad, beneficial or not as a result of their education”. He was convinced that there is an unbreakable connection between three areas of education: the moral, mental and physical. Of those three he considered moral education as the most important. He stressed that the aim of education is to guide a person in such a way that enables them to control their aspirations, desires and affections with the mind – and that such skills are the basis of virtue. According to Locke, without virtue and self-discipline it is difficult to act in a reasonable way. He recognised people’s individualism, so he recommended that the methods of education should be fitted to the abilities of the child. He called for the replacement of orders and prohibitions with explanation, habituation, understanding and experience. A child needs to be taught, among other things, to appreciate truth, honesty, respect for others, kindness and restraint from cruelty towards people and animals. According to Locke, this should lead to correct shaping of moral character.